“Efecto de biorreguladores sobre el crecimiento y rendimiento de lechuga crespa (Lactuca sativa)”. - Caballero Tapia, Kevin Renan (2023)
The current research was carried out in El Progreso Campus in Pujilí Canton in Cotopaxi Province and net lasted 60 days. The objective is to evaluate the effect of bioregulators on the growth and yield of crisp lettuce (Lactuca sativa). In the investigation, a completely randomized block design (DBCA) was used, with five treatments and five repetitions, making up a total of twenty-five experimental units with the following variables: plant height (cm), number of leaves (unit), leaf length (cm), leaf width (cm), cabbage equatorial diameter, plant net weight (g), plot weight (kg), yield (kg/ha). In the investigation, the best performance was obtained by the brassinosteroids treatment with a value of 18933.33 kg/ha. As a result that brassinosteroids are a reliable alternative for the production of crisp lettuce. To conclude, bioregulators are recommended for the economic axis in lettuce cultivation since they all give us a high net benefit, making it economically suitable for farmers. Finally, gibberellin obtained the highest net income with $19.81.